Perpetrators of mass atrocities: terribly and terrifyingly normal? - Smeulers, Alette (Routledge, 2024)
Drawing on thirty years of research, in this book Alette Smeulers explores the perpetrators of mass atrocities such as war crimes, crimes against humanity, genocide and terrorism